Actin stabilization in cell migration - Baltes, Carsten; Thalla, Divyendu Goud; Kazmaier, Uli; Lautenschläger, Franziska (Frontiers in Cell and Developmental Biology, 2022)
Actin is a cytoskeletal filament involved in multitude of biological tasks, such as providing cells a shape or generating and transmitting forces. Particular important for these tasks is the ability of actin to grow and shrink. To study the role of actin in living cells this dynamic needs to be targeted. In the past, such alterations were performed by destabilizing actin. In contrast, we use the natural compound miuraenamide A in living RPE-1 cells to stabilize actin filaments and show that it decreases the actin filament dynamics and elongates filament length. Cells treated with miuraenamide A increase their adhesive area and express more focal adhesion sites. These alterations result in a lower migration speed as well as a shift of nuclear position. We therefore postulate that miuraenamide A is a promising new tool to stabilize actin polymerization and study cellular behavior such as migration.